BNT162B2 mRNA COVID-19 Vaccine in Heart and Lung Transplanted Young Adults: Is an Alternative SARS-CoV-2 Immune Response Surveillance Needed?. Issue 2 (21st December 2021) - Cotugno, Nicola; Pighi, Chiara; Morrocchi, Elena; Ruggiero, Alessandra; Amodio, Donato; Medri, Chiara; Colagrossi, Luna; Russo, Cristina; Di Cesare, Silvia; Santilli, Veronica; Manno, Emma Concetta; Zangari, Paola; et al.
Abstract : Abstract :